Evaluasi Penerapan Program Lumbung Pangan Masyarakat di Subak Seronggo Desa Pangkungkarung Kecamatan Kerambitan Kabupaten Tabanan - WISMAYA, I GEDE DAKSA; SUTJIPTA, I NYOMAN; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Implementation Evaluation of food Barn Communities Program in Subak Seronggo, Pangkungkarung Village, Sub District Kerambitan, Tabanan Regency The economic crisis in 1998 has affected the national food security in household sphere. Food security is the strength of a nation to maintain the stability of national food and thus, the government established a program focuses on maintaining the stability of national food security using food barn communities program. Each program developed by the government needs someone to evaluate it so there will be indicator of the program success. The purpose of the research is finding out the food barn program evaluation in Subak Seronggo. This research was conducted in Subak Seronggo, Pangkungkarung Village, Sub District Kerambitan, Tabanan Regency. The population of Subak Seronggo is 100 people. The determination of samples uses simple random sampling. Respondent were drawn by 50 people. The result is showed on the growth phase that the government gives the requirement used to run the food barns program. The development phase can be categorized as a good achievement with score (3,71), the autonomy phase can be categorized in medium level of achievements with score (3,33). The result is in good level of achievements with score (3,98). Based on the result, the food mow in the Subak Seronggo is categorized as good, it is because the members manage and utilize the aid using the agreement that formed according to the group deals so that the social discrepancy in the group can be avoided.
Keywords: endurance of food; food barn; evaluation program